Is There a Foster Care-To-Prison Pipeline? Evidence from Quasi-Randomly Assigned Investigators - Baron, E. Jason; Gross, Max (The Review of Economics and Statistics, 2025)
Foster care placement is strongly associated with crime—for example, close to one fifth of the prison population in the U.S. is comprised of former foster children—yet there is little evidence on whether this relationship is causal. Leveraging the quasi-random assignment of investigators and administrative data from Michigan, we show that placement substantially reduced the chances of adult arrests, convictions, and incarceration for children at the margin. Exploring mechanisms, we find evidence that children’s birth parents made positive changes following placement. We show that most children in our setting reunified with their parents after being in foster care for one to two years, and that parents themselves were less likely to have criminal justice contact after placement. Considering recent historic federal policy which prioritizes keeping children with their families, our analysis indicates that safely reducing foster care caseloads will require improving efforts to ensure child wellbeing in the home.